(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the theoretical interpretation of symmetrical and asymmetrical phenomena in linguistics and their role in the language system. The study analyzes the relationship between form and content between linguistic units, their compatibility or incompatibility. It is shown that symmetry expresses a balanced, harmonious relationship between form and content in the language system, while asymmetry manifests itself in such phenomena as disproportion, ambiguity, synonymy and homonymy between them